2018
DOI: 10.3846/transport.2018.5400
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Knowledge Level of Stakeholders on Transport Interchange Design and Operation

Abstract: The paper advances the results of the on-going work conducted within the frame of the European Twinning project ALLIANCE. In the effort to assess educational needs of different stakeholder groups involved in the domain, this paper’s main interest is to study knowledge and importance of governance issues and smart solutions, which enable smooth and seamless interconnectivity of alternative transportation modes, and techniques for facilitating decision-making and evaluation of these solutions. Data were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…For instance, Nerhagen (2003) revealed that personal transport choice does not refer only to habitual behavior, but it reflects also the previous experience and the good knowledge of a specific travel mode without knowing the aspects of other modes. Moreover, Yatskiv et al (2018) conducted a survey study in Latvia to investigate the LoK, of different stakeholders, on strategies and policies relevant to transport modes. Policymakers, transport industry experts, students and researchers represent the main population groups of the survey.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Nerhagen (2003) revealed that personal transport choice does not refer only to habitual behavior, but it reflects also the previous experience and the good knowledge of a specific travel mode without knowing the aspects of other modes. Moreover, Yatskiv et al (2018) conducted a survey study in Latvia to investigate the LoK, of different stakeholders, on strategies and policies relevant to transport modes. Policymakers, transport industry experts, students and researchers represent the main population groups of the survey.…”
Section: Introductionmentioning
confidence: 99%